The Measurement of Atmospheric Species with Absorptions Close to the Actinic Flux Cut-Off by Active & MAX-DOAS: Chlorine Monoxide (CIO) & Sulphur Dioxide (SO2) - Csukat, Csilla Edina (2019)
The gas-phase chlorine monoxide (ClO) radical has been studied extensively for its role in catalytic stratospheric ozone depletion following the discovery of the Antarctic ozone hole in 1985. Reactive chlorine chemistry is known to occur in the troposphere as well, originating primarily from sea salt aerosols in the marine boundary layer, but direct spectroscopic observations have been limited. In this research, we endeavour to identify and quantify ClO in a mid-latitude urban atmosphere removed from a large source of salt water, using techniques of differential optical absorption spectroscopy (DOAS). In particular, we seek to determine whether this trace gas is present in any appreciable amount in ambient air during the wintertime owing to the widespread application of road salt. The study was performed at The Centre for Atmospheric Chemistry at York University in Toronto, Ontario, Canada (43.77 N, 79.50 W) using Active long-path DOAS and MAX-DOAS.